1995
DOI: 10.1073/pnas.92.5.1679
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic inhibition of carotenoid biosynthesis with virus-derived RNA.

Abstract: The carotenoid biosynthetic pathway in higher plants was manipulated by using an RNA viral vector. A cDNA encoding phytoene synthase and a partial cDNA encoding phytoene desaturase (PDS) were placed under the transcriptional control of a tobamovirus subgenomic promoter. One to two weeks after inoculation, systemically infected Nicotiana benthamiana plants were analyzed for phytoene. Leaves from transfected plants expressing phytoene synthase developed a bright orange phenotype and accumulated high levels of ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
414
0
11

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 631 publications
(439 citation statements)
references
References 18 publications
14
414
0
11
Order By: Relevance
“…High levels of phytoene also accumulated in photobleached, transfected leaves of N. benthamiana by silencing the expression of the downstream enzyme phytoene desaturase using fragments of a gene derived from tomato and cloned in either the sense or antisense orientation (Kumagai et al 1995). Therefore, the virus-induced gene silencing originally observed to target viral-derived transgenes (Lindbo et al 1993) can be widely and conveniently applied in functional genomics studies.…”
Section: (B) Metabolic Pathways and Gene Functionmentioning
confidence: 99%
“…High levels of phytoene also accumulated in photobleached, transfected leaves of N. benthamiana by silencing the expression of the downstream enzyme phytoene desaturase using fragments of a gene derived from tomato and cloned in either the sense or antisense orientation (Kumagai et al 1995). Therefore, the virus-induced gene silencing originally observed to target viral-derived transgenes (Lindbo et al 1993) can be widely and conveniently applied in functional genomics studies.…”
Section: (B) Metabolic Pathways and Gene Functionmentioning
confidence: 99%
“…It has been reported that VIGS of PDS resulted in a photobleached phenotype (Kumagai et al, 1995;Liu et al, 2002a). Two-leaf-stage barley plants were inoculated with saps of N. benthamiana leaves agroinfiltrated with FoMV-HvPDS200 or empty vector pFoMV-sg.…”
Section: Fomv-based Vigs In Barleymentioning
confidence: 99%
“…The cDNA fragments (0.5 kb) corresponding N. benthamiana (Nb SAMT1) and Pantoea agglomerans phytoene synthase (CrtB; P22872), used as a control, were amplified by PCR and cloned into the viral vector TTO (Kumagai et al, 1995). For TTO-Nb SAMT1, the forward primer 59-GCCTCGAGTTGAAGATGCTTCCTGAAAATCTTAGTGC-39 and the reverse primer 5-TCCCTAGGCCAAAGCACTCTTGGACCGATGCCCTT-39 containing XhoI and AvrII restriction sites, respectively, were used.…”
Section: Virus-induced Gene Silencingmentioning
confidence: 99%